Iron Regulation: Macrophages in Control - Nyamdelger Sukhbaatar; Thomas Weichhart (MDPI AG, 2018)
Macrophages are sentinel cells of the innate immune system and have important functions in development, tissue homeostasis, and immunity. These phylogenetically ancient cells also developed a variety of mechanisms to control erythropoiesis and the handling of iron. Red pulp macrophages in the spleen, Kupffer cells in the liver, and central nurse macrophages in the bone marrow ensure a coordinated metabolism of iron to support erythropoiesis. Phagocytosis of senescent red blood cells by macrophages in the spleen and the liver provide a continuous delivery of recycled iron under steady-state conditions and during anemic stress. Central nurse macrophages in the bone marrow utilize this iron and provide a cellular scaffold and niche to promote differentiation of erythroblasts. This review focuses on the role of the distinct macrophage populations that contribute to efficient iron metabolism and highlight important cellular and systemic mechanisms involved in iron-regulating processes.